Cost effectiveness analysis of using different monitoring modalities in treating severe traumatic brain injury (CESTBI) in neuro-ICU, HUSM, Kelantan - Mohd Ismail I; Mazlan A; Naing L; Jafri Malin A (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
Introduction: There are two schools of thought in practicing neurotrauma monitoring for patients with severe traumatic brain injury (TBI); the application of the baseline neuro-monitoring (BNM) and the use of multiple modalities neurotrauma monitoring (M3) which is very expensive. The answer of which of the two monitoring systems is more eflicient and worth doing should be sought. Objective: To determine the cost effectiveness analysis between BNM and M3 monitoring modalities in the management of severe TBI. Methodology: Sixty-two patients with severe TBI admitted to Neuro-ICU, USM who fulfilled the predetermined criteria were selected using systematic random sampling. The macro and micro costing were performed on each of patient. Barthel Index was used to measure physical performance as an outcome six months after discharge. The analyses used were the Independent t- test, ANCOVA, and Repeated Measure ANOVA. Results: The mean total equipment cost of M3 was significantly higher at p = 0.049 (mean difference of RM23.74) after controlling other variables. The mean difference in Barthel Index after six months was significance between the two groups (p = 0.031), patients that were treated with M3 had higher score 163.7 (SD 30.03)J compared to those who were treated with BNM 146.83 (SD 30.36)]. However, the cost-effectiveness ratio of using M3 was significantly lowered (p=O.031) with a mean of RM476.29 was needed to increase a unit improvement in mean Barthel Index compared to RM629.12 if we used BNM. Conclusion: Although M3 is more costly, the outcome of patients treated with M3 was better than that of BNM. Therefore we can conclude that the used of multiple neuro-monitoring was more cost effective than the use of only baseline neuro-monitoring in treating severe traumatic brain injury.